Recent developments in the asymmetric Reformatsky-type reaction - Pellissier, Hélène (Beilstein Journal of Organic Chemistry, 2018)
This review collects the most important developments in asymmetric Reformatsky-type reactions published since the beginning of 2013, including both diastereoselective methodologies based on the use of chiral substrates and enantioselective catalytic procedures.
Keywords: asymmetric (aza)-Reformatsky reaction; asymmetric synthesis; chirality; diastereoselectivity; enantioselectivity; total synthesis